The United States' New Military Act Policy Causes China to be Angry because Interfering in to Taiwan Issue - Ma Tian Yu (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
This study aims to analyze international policies, especially the military and politics of major countries, including the US and China. It should be noted that several months ago US government representatives made political visits to Taiwan, even as much as 2x, this is very sensitive regarding the heating up relations between China and Taiwan. Plus the Chinese Government expressed anger at the United States defense law that increased military assistance to Taiwan. Meanwhile Taiwan supports the new US law because it helps improve the security of the island. China, which regards democratically-ruled Taiwan as its own territory, expressed